Newton’s methodology and the demonstration of the reality of the force - Molina Betancur, Sebastián (Estudios de Filosofía, 2014)
Some experts on Newton have argued that the methodology that he uses to demonstrate the existence of force is based on his mathematical approach to the phenomena of movement, which has come to be understood as a classical interpretation of the subject. However, if examined under the light of the interpretation given by authors like Guicciardini and Guerlac, this interpretation has many limitations. This article shows the limitations of the classical interpretation in light of this recent interpretation by exploring the methodological aspects of the demonstration of force.